Magnetic and transport properties of charge ordered La₀.₅Ca₀.₅Mn₀.₃ and La₀.₄Ca₀.₆Mn₀.₃ films - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Lee, Y.P.; Park, S.Y.; Hyun, Y.H.; Svetchnikov, V.L.; Kim, K.W.; Rhee, J.Y. (Физика низких температур, 2006)
The magnetic and the transport properties of La₀.₅Ca₀.₅Mn₀.₃ and La₀.₄Ca₀.₆Mn₀.₃ films with
different thickness, prepared by rf-magnetron sputtering by using the so-called «soft» (or powder)
target on LaAlO₃ substrate, have been investigated. The electron-diffraction and the high-resolution
electron microscopy (HREM) studies show that the charge-ordered phase is observed at room
temperature for all films. Both the paramagnetic-to-ferromagnetic transition at TC ≈ 250 K upon
cooling and the appearance of an antiferromagnetic (AFM) phase at TN ≧ 140 K were observed in
the La₀.₅Ca₀.₅Mn₀.₃ films, while the La₀.₄Ca₀.₆Mn₀.₃ films exhibited the AFM transition only at
the same temperature, excepting the small ferromagnetic (FM) response from a «dead» layer. It
was shown that the volume fraction of the FM phase in the La₀.₅Ca₀.₅Mn₀.₃ film did not exceed of
and the FM phase coexisted with the AFM one at low temperature. All films manifest an exponential
temperature dependence of resistance without evidence of the metal-insulator transition. This
is explained by the scarcity of the FM phase for the formation of infinite percolating cluster and
by an existence of the charge-ordered phase. The field-dependent magnetoresistance at low temperature
is described in terms of the spin-assisted polaron-hopping model.